Our friend hedgehog : the story of us - Castillo, Lauren (New York : Alfred A. Knopf, 2020)
When a storm separates Hedgehog from her lifelong friend, Mutty, she bravely sets out to find him and makes some very good new friends in the process.
School Library Journal, May 2020
Booklist starred, March 2020
Publishers Weekly, March 2020
Kirkus Starred, March 2020
2.4
Texas Bluebonnet Award, 2021
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Hedgehogs -- Juvenile fiction; Animals -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Hedgehogs -- Fiction; Animals -- Fiction; Animal fiction